A high-strength wear-resistant silicon nitride bonded silicon carbide ceramic and preparation method thereof

Through high-solid-phase slurry spray granulation and composite molding processes, fibrous silicon nitride crystals and ZrSi2N4 are generated in situ, solving the problem of poor performance of existing silicon nitride combined with silicon carbide ceramics in advanced powder technology and harsh environments, and achieving high-strength, high-hard, and high-strength ceramic materials, significantly improving wear resistance and corrosion resistance.

CN116903376BActive Publication Date: 2025-03-11JIANGSU TAIRUI REFRACTORY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310832443.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-03-11
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

When used in more advanced powder crushing and grinding technology and harsh environments, existing silicon nitride combined with silicon carbide ceramic materials have poor uniformity, poor mechanical properties, and short service life, making it difficult to meet the high requirements of modern industry.

Method used

The high-solid-phase slurry spray granulation process and composite molding process are adopted to form liquid-phase dissolved α-Si3N4 through tempering agents such as Y2O3 and promote the growth of β-Si3N4, and fiber-like and columnar silicon nitride crystals are generated in situ, and ZrSi2N4 is formed under high temperature and high pressure environment to improve the density and uniformity of the ceramic.

Benefits of technology

It significantly improves the wear resistance, corrosion resistance and impact resistance of silicon nitride combined with silicon carbide ceramics, adapts to the service environment of fast continuous impact, high hardness materials and corrosive materials, extends service life, improves production efficiency and reduces material pollution.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of wear-resistant ceramics, and in particular to a high-strength wear-resistant silicon nitride combined with silicon carbide ceramic and a preparation method thereof. The high-strength wear-resistant silicon nitride combined with silicon carbide ceramic is prepared from simple silicon powder, silicon carbide powder, silicon nitride powder, a tempering agent, and a binder: the tempering agent includes Y2O3 micro-nano particles, zirconium carbide powder, zirconium powder, and tungsten carbide. The reaction sintering silicon nitride combined with silicon carbide process is adopted, and the microstructure and phase composition are optimized and controllably prepared under the coupling effect of the composite tempering agent and the in-situ generated controllable fibrous and columnar Si3N4; ZrSi2N4 and silicon nitride can form a good chemical bond. The wear-resistant ceramic prepared by the method has the characteristics of high strength, high hardness, and high toughness, and the wear resistance, corrosion resistance, and impact resistance are significantly improved, the service life is extended, and the production efficiency of related industries is greatly improved. At the same time, the pollution to the material is reduced, the high performance and stability of the product are guaranteed, and it has obvious economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wear-resistant ceramics, and in particular to a high-strength wear-resistant silicon nitride combined with silicon carbide ceramic and a preparation method thereof. Background Art

[0002] Wear-resistant materials are widely used in various fields of industrial production. With the rapid development of science and technology and modern industry, the development of wear-resistant materials has become an important factor affecting the production efficiency of modern industry.

[0003] For example, in powder production, from raw material mining, crushing, grinding and ultrafine grinding technology of micro-nano powders, wear-resistant materials run through the entire production process. The service performance of wear-resistant materials directly determines the cost and quality of powder processing. The demand for micro-nano powders in the modern industrial system is increasing, and higher requirements are put forward for grinding technology, such as planetary ball milling: ball milling jars and ball milling beads are parts that are in direct contact with materials during the powder process. Their main materials are high chromium alloys, medium and high carbon steels, agates, etc. It is difficult to achieve a balance between the mechanical toughness, impact resistance and wear resistance of metal materials. After ball milling high-hardness materials, it is easy to peel off and break, which not only shortens the service life, but also causes pollution to the materials by the peeling metal. The natural agate material is expensive and not easy to be made into large-volume ball mills, which has an adverse effect on industrial production. In addition, in the metallurgical, cement, and glass industries, the application of wear-resistant materials is more extensive, such as rollers in hot rolling links, aluminum alloy die-casting tubes, cement rotary kiln mouths, glass annealing kiln wear-resistant support plates, etc. Wear-resistant materials have become the mainstay of industrial production. Existing wear-resistant materials are difficult to adapt to the production needs of the current market.

[0004] Silicon nitride bonded with silicon carbide is a high-performance ceramic material with Si3N4 as the main bonding phase and one or more carbides, nitrides, and oxides as reinforcing phases. It has excellent corrosion resistance, erosion resistance, and good comprehensive mechanical properties such as hardness, toughness, and wear resistance. Compared with other non-oxide ceramics such as recrystallized silicon carbide, it has a price advantage. Therefore, silicon nitride bonded with silicon carbide materials are widely used in non-ferrous metallurgy, steel smelting, petrochemicals, automobile manufacturing and other fields. However, the existing production process of silicon nitride bonded with silicon carbide uses refractory-grade raw materials and relatively backward mixing and molding processes. The silicon nitride bonded with silicon carbide produced has poor uniformity, poor mechanical properties, and a short lifespan, making it difficult to be used in more advanced powder crushing and grinding technologies and harsher use environments.

[0005] Therefore, we proposed a high-strength and wear-resistant silicon nitride combined with silicon carbide ceramic and a preparation method to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-strength and wear-resistant silicon nitride combined with silicon carbide ceramic and a preparation method thereof.

[0007] A high-strength wear-resistant silicon nitride combined with silicon carbide ceramic is prepared from the following raw materials in parts by weight:

[0008] 65-85 parts of silicon powder, 15-35 parts of silicon carbide powder, 5-10 parts by weight of silicon nitride powder, 1-5 parts of conditioning agent, and 0.5-10 parts of binder;

[0009] The conditioning agent comprises 5 to 10 parts by weight of Y2O3 micro-nano particles, 5 to 8 parts by weight of zirconium carbide powder, 5 to 8 parts by weight of zirconium powder, and 1 to 3 parts by weight of tungsten carbide.

[0010] Preferably, the particle size of the elemental silicon powder is 200-600 mesh, and the particle size of the silicon carbide powder is 200-600 mesh.

[0011] Preferably, the particle size of the silicon nitride is 600-1000 mesh.

[0012] Preferably, the binder is one or more of polyvinyl alcohol, dextrin, phenolic resin, arabic resin, lignin, phosphate and hydroxymethyl cellulose.

[0013] A method for preparing high-strength wear-resistant silicon nitride-bonded silicon carbide ceramics comprises the following steps:

[0014] S1. Add the raw materials, anhydrous ethanol and grinding balls into a high-speed mixer and premix for 15 min to 12 h, then add 5 to 50% of the mass of the raw materials in deionized water, and place in a high-speed ball mill for 15 min to 12 h to obtain a slurry;

[0015] S2, drying the slurry obtained in step S1 at 100-300° C. using a spray granulation device to obtain a granulated material with uniform and stable dispersion and a particle size of 0.01-1.5 mm;

[0016] S3, putting the granulated material obtained in step S2 into an extruder, extruding and molding to obtain a ceramic blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding to obtain a uniform and dense ceramic blank;

[0017] S4. Place the ceramic tube blank obtained in step S3 in a high-temperature atmosphere sintering furnace, heat it to 800-1000°C at a heating rate of 10-30°C / min under a nitrogen atmosphere, keep it warm for 0.5-3 h, then heat it to 1200-1400°C at a heating rate of 10-30°C / min, keep it warm for 1-3 h, then heat it to 1500-1700°C at a heating rate of 10-30°C / min, keep it warm for 3-6 h, to obtain high-strength and wear-resistant silicon nitride bonded silicon carbide ceramics.

[0018] Preferably, in step S1, the rotation speed of the high-speed ball mill is 100 r / min to 360 r / min, the grinding balls are one or more of agate ball milling beads, stainless steel ball milling beads and corundum ball milling beads, the particle size is 1 to 10 mm, and the protective atmosphere is vacuum, argon, nitrogen or a composite atmosphere thereof.

[0019] Preferably, in step S1, the mass ratio of the raw material, anhydrous ethanol and grinding balls is 1:4-8:2-6.

[0020] Preferably, in step S2, after the granulated material is dried, it is sealed at a temperature of 28 to 32° C. for 12 to 36 hours.

[0021] Preferably, in step S3, the isostatic pressure is 150-200 MPa.

[0022] The beneficial effects of the present invention are:

[0023] The present invention utilizes a high solid phase slurry spray granulation process to evenly mix components with greatly different contents in the raw materials, thereby ensuring that the components and structures of various parts of the product are uniform.

[0024] The present invention adopts a composite molding process, which improves the density and uniformity of ceramics, improves the comprehensive mechanical properties and thermal shock stability of the product, greatly reduces the raw material consumption caused by machining, and greatly increases product profits for production enterprises.

[0025] The wear-resistant ceramics prepared by this method dissolve α-Si3N4 in a nitrogen atmosphere through a liquid phase formed by a conditioning agent such as Y2O3 and promote the growth of β-Si3N4, generating fibrous and columnar silicon nitride crystals in situ in the material; at the same time, in a high temperature and high pressure environment, ZrSi2N4 with ultra-high hardness, high thermal stability and corrosion resistance is generated in situ, which can form a good chemical bond with silicon nitride. And under the coupling effect of the composite conditioning agent, the silicon nitride combined with silicon carbide ceramics has the characteristics of high strength, high hardness and high toughness in all directions. At the same time, the controllable preparation of microstructure and phase composition has a high adaptability to service environments of different shapes and requirements, and the wear resistance, corrosion resistance and impact resistance are significantly improved. It can adapt to the service environment of rapid continuous impact, high hardness materials, and corrosive materials (atmosphere), and the continuous working time is increased, which greatly improves the production efficiency of ultrafine powders, while reducing the pollution of materials, ensuring the high performance and stability of the product, and has obvious economic benefits. DETAILED DESCRIPTION

[0026] The present invention will be further explained below in conjunction with specific embodiments.

[0027] Example 1: A high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic is prepared from the following raw materials in parts by weight:

[0028] 75 parts of elemental silicon powder with a particle size of 400 mesh, 25 parts of silicon carbide powder with a particle size of 400 mesh, 5 parts by weight of silicon nitride powder with a particle size of 800 mesh, 2 parts of a conditioning agent, and 3 parts of a phenolic resin binder;

[0029] The conditioning agent includes 8 parts by weight of Y2O3 micro-nano particles, 6 parts by weight of zirconium carbide powder, 6 parts by weight of zirconium powder, and 2 parts by weight of tungsten carbide.

[0030] A method for preparing high-strength wear-resistant silicon nitride-bonded silicon carbide ceramics comprises the following steps:

[0031] S1. The raw materials, anhydrous ethanol and 5 mm grinding balls were accurately weighed according to the mass ratio of 1:6:4, added to a high-speed mixer for premixing for 45 min, and then 30% of the raw material mass of deionized water was added, and placed in a high-speed ball mill at 200 r / min, and ball milled for 45 min under a nitrogen atmosphere to obtain a slurry; the grinding balls were agate ball milling beads.

[0032] S2. Dry the slurry obtained in step S1 at 200°C using a spray granulation device to obtain granules with uniform and stable dispersion and a particle size of 0.5 mm, and then seal the granules at 30°C for 24 hours.

[0033] S3, putting the granulated material obtained in step S2 into an extruder, extruding and molding to obtain a ceramic blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding at a pressure of 180 MPa to obtain a uniform and dense ceramic blank;

[0034] S4. Place the ceramic tube blank obtained in step S3 in a high-temperature atmosphere sintering furnace, heat it to 900°C at a heating rate of 20°C / min under a nitrogen atmosphere, keep it warm for 2 hours, then heat it to 1300°C at a heating rate of 20°C / min, keep it warm for 2 hours, then heat it to 1600°C at a heating rate of 20°C / min, keep it warm for 5 hours, to obtain high-strength and wear-resistant silicon nitride bonded silicon carbide ceramics.

[0035] Example 2: A high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic is prepared from the following raw materials in parts by weight:

[0036] 70 parts of elemental silicon powder with a particle size of 400 mesh, 30 parts of silicon carbide powder with a particle size of 400 mesh, 5 parts by weight of silicon nitride powder with a particle size of 800 mesh, 3 parts of a conditioning agent, and 2 parts of a polyvinyl alcohol binder;

[0037] The conditioning agent includes 6 parts by weight of Y2O3 micro-nano particles, 7 parts by weight of zirconium carbide powder, 7 parts by weight of zirconium powder, and 2 parts by weight of tungsten carbide.

[0038] A method for preparing high-strength wear-resistant silicon nitride-bonded silicon carbide ceramics comprises the following steps:

[0039] S1. The raw materials, anhydrous ethanol and 5 mm grinding balls were accurately weighed according to the mass ratio of 1:6:4, added to a high-speed mixer for premixing for 45 min, and then 35% of the raw material mass of deionized water was added, and placed in a high-speed ball mill at 200 r / min, and ball milled for 45 min under an argon atmosphere to obtain a slurry; the grinding balls were stainless steel ball milling beads.

[0040] S2. Dry the slurry obtained in step S1 at 200°C using a spray granulation device to obtain granules with uniform and stable dispersion and a particle size of 1 mm, and then seal the granules at 30°C for 24 hours.

[0041] S3, putting the granulated material obtained in step S2 into an extruder, extruding and molding to obtain a ceramic blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding at a pressure of 180 MPa to obtain a uniform and dense ceramic blank;

[0042] S4. Place the ceramic tube blank obtained in step S3 in a high-temperature atmosphere sintering furnace, heat it to 1000°C at a heating rate of 20°C / min under a nitrogen atmosphere, keep it warm for 1 hour, then heat it to 1300°C at a heating rate of 20°C / min, keep it warm for 2 hours, and then heat it to 1600°C at a heating rate of 20°C / min, keep it warm for 5 hours to obtain high-strength and wear-resistant silicon nitride bonded silicon carbide ceramics.

[0043] Example 3: A high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic is prepared from the following raw materials in parts by weight:

[0044] 80 parts of elemental silicon powder with a particle size of 400 mesh, 20 parts of silicon carbide powder with a particle size of 400 mesh, 5 parts by weight of silicon nitride powder with a particle size of 800 mesh, 4 parts of a conditioning agent, and 4 parts of an Arabic resin binder;

[0045] The conditioning agent includes 6 parts by weight of Y2O3 micro-nano particles, 7 parts by weight of zirconium carbide powder, 5 parts by weight of zirconium powder, and 2 parts by weight of tungsten carbide.

[0046] A method for preparing high-strength wear-resistant silicon nitride-bonded silicon carbide ceramics comprises the following steps:

[0047] S1. The raw materials, anhydrous ethanol and 5 mm grinding balls were accurately weighed according to the mass ratio of 1:6:4, added to a high-speed mixer for premixing for 45 min, and then 30% of the raw material mass of deionized water was added, and placed in a high-speed ball mill at 200 r / min, and ball milled for 45 min under a nitrogen atmosphere to obtain a slurry; the grinding balls were corundum ball milling beads.

[0048] S2. Dry the slurry obtained in step S1 at 200°C using a spray granulation device to obtain granules with uniform and stable dispersion and a particle size of 0.5 mm, and then seal the granules at 30°C for 24 hours.

[0049] S3, putting the granulated material obtained in step S2 into an extruder, extruding and molding to obtain a ceramic blank, and then isostatically pressing the ceramic tube blank obtained by extrusion molding at a pressure of 180 MPa to obtain a uniform and dense ceramic blank;

[0050] S4. Place the ceramic tube blank obtained in step S3 in a high-temperature atmosphere sintering furnace, heat it to 900°C at a heating rate of 20°C / min under a nitrogen atmosphere, keep it warm for 2 hours, then heat it to 1200°C at a heating rate of 20°C / min, keep it warm for 2 hours, then heat it to 1600°C at a heating rate of 20°C / min, keep it warm for 5 hours, to obtain high-strength and wear-resistant silicon nitride bonded silicon carbide ceramics.

[0051] Comparative Example:

[0052] A silicon nitride-bonded silicon carbide material tube is prepared from the following raw materials in parts by weight:

[0053] 10 parts by weight of elemental silicon powder, 20 parts by weight of silicon nitride powder, and 20 parts by weight of silicon carbide powder.

[0054] The preparation method comprises the following steps:

[0055] S1. Mix elemental silicon powder, silicon nitride powder and silicon carbide powder at 60° C. for 1.5 h to obtain a uniform mixture;

[0056] S2, drying the mixture prepared in step S1 at a temperature of 200° C. and a humidity of 3% for 5 h, and sealing the mixture for 36 h to obtain a formed mixture;

[0057] S3, forming the mixed material obtained in step S2 by friction forming to obtain a raw material tube blank;

[0058] S4. Place the raw material tube blank obtained in step S3 in a high-temperature furnace, a box-type carbonization furnace, and sinter under the protection of a nitrogen atmosphere. Heating the temperature to 1200° C. at a heating rate of 60° C. / h, and keeping the temperature for 2 hours to obtain a raw material tube.

[0059] The mechanical properties and thermal shock stability tests were conducted on the silicon nitride combined with silicon carbide ceramic material tubes in Examples 1 to 3 and the comparative example. The test results are as follows:

[0060] Among them, the hardness is the Vickers hardness at room temperature, and the testing standard is GB / T 16534-2009; the thermal expansion coefficient is the linear thermal expansion coefficient between 20℃~300℃, and the testing standard is YS / T 63.4-2006; the thermal shock cracking test is the residual strength retention rate after water cooling at 1000℃, and the testing standard is YB 4018-91; the thermal conductivity coefficient, the testing standard is GB / T 39862-2021; the wear resistance coefficient is the wear resistance at room temperature, and the testing standard is GB / T 18301-2012.

[0061] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramics, characterized in that: The following steps are involved: S1. Add 65-85 parts by weight of elemental silicon powder, 15-35 parts by weight of silicon carbide powder, 5-10 parts by weight of silicon nitride powder, 1-5 parts by weight of a conditioning agent, 0.5-10 parts by weight of a binder, anhydrous ethanol and grinding balls into a high-speed mixer and premix for 15 min to 12 h, then add 5-50% of the mass of the above raw materials in deionized water, and place in a high-speed ball mill for 15 min to 12 h to obtain a slurry; The conditioning agent includes 5 to 10 parts by weight of Y2O3 micro-nano particles, 5 to 8 parts by weight of zirconium carbide powder, 5 to 8 parts by weight of zirconium powder, and 1 to 3 parts by weight of tungsten carbide; S2, drying the slurry obtained in step S1 at 100-300° C. using a spray granulation device to obtain a granulated material with uniform and stable dispersion and a particle size of 0.01-1.5 mm; S3, putting the granulated material obtained in step S2 into an extruder, extruding and molding to obtain a ceramic green blank, and then isostatically pressing the ceramic green blank obtained by extrusion molding at an isostatic pressing pressure of 150-200 MPa to obtain a uniform and dense ceramic green blank; S4. Place the ceramic green body obtained in step S3 in a high-temperature atmosphere sintering furnace, heat it to 800-1000°C at a heating rate of 10-30°C / min under a nitrogen atmosphere, keep it warm for 0.5-3h, then heat it to 1200-1400°C at a heating rate of 10-30°C / min, keep it warm for 1-3h, then heat it to 1500-1700°C at a heating rate of 10-30°C / min, keep it warm for 3-6h, to obtain high-strength and wear-resistant silicon nitride bonded silicon carbide ceramics.

2. The method for preparing a high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic according to claim 1, characterized in that: In step S1, the binder is one or more of polyvinyl alcohol, dextrin, phenolic resin, arabic resin, lignin, phosphate and hydroxymethyl cellulose.

3. The method for preparing a high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic according to claim 1, characterized in that: In step S1, the particle size of the elemental silicon powder is 200-600 mesh, and the particle size of the silicon carbide powder is 200-600 mesh.

4. The method for preparing a high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic according to claim 1, characterized in that: In step S1, the particle size of the silicon nitride powder is 600-1000 mesh.

5. The method for preparing a high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic according to claim 1, characterized in that: In step S1, the rotation speed of the high-speed ball mill is 100 r / min to 360 r / min, the grinding balls are one or more of agate ball milling beads, stainless steel ball milling beads and corundum ball milling beads, the particle size is 1 to 10 mm, and the protective atmosphere is argon, nitrogen or their composite atmosphere.

6. The method for preparing a high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic according to claim 1, characterized in that: In step S1, the mass ratio of the raw material, anhydrous ethanol and grinding balls is 1:4-8:2-6.

7. The method for preparing a high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic according to claim 1, characterized in that: In step S2, after the granulated material is dried, it is sealed and trapped at a temperature of 28 to 32° C. for 12 to 36 hours.

8. A high-strength and wear-resistant silicon nitride-bonded silicon carbide ceramic, characterized in that: The high-strength and wear-resistant silicon nitride combined with silicon carbide ceramic is obtained by the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-strength silicon nitride composite silicon carbide ceramic as well as preparation method and application thereof

    CN111499387A

  • High-hardness silicon nitride ceramic and preparation method thereof

    CN111908923A

  • Alumina antistatic ceramic and preparation method thereof

    CN115448742A